CHARACTERISTIC OF FISH GLUE FROM THREE DIFFERENT MARINE FISHES - Edo Prabawandwika Sulistyanto; Yudhomenggolo Sastro Darmanto; Ulfah Amalia (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
Fish bone waste is a byproduct of fish processing units, which can be utilized to produce fish glue. Fish glue is an adhesive substance that made from collagen extract of fish skin and bones. The purpose of this research was to determine the quality of the fish glue with different raw materials of marine fishes bones such as Spanish Mackerel (Scomberomorus commerson), Eastern little Tuna (Euthynnus affinis), and Cobia (Rachycentron canadum). The research method was the extraction of fish bones using 5% CH3COOH solution with a ratio of fish bone and solution of 1:1.  Later, the filtrate was evaporated using a rotary vacuum evaporator to obtain fish glue. Parameters measured were bonding strength, damage to wooden surfaces, viscosity, pH, and moisture content. The results showed that the use of raw materials of different fish bones affect the value of the bonding strength, damage to wooden surfaces, viscosity, pH, and moisture content. Fish glue made of Eastern little Tuna bones as raw material was the best product resulted from this research, with the fish glue characteristics for bonding strength of 7.7 N/mm2, wood surface damage of 83.21%, viscosity of 4.17 poise, pH 4.74, and moisture content of 55.60%. The product was also comply with SNI 06-6049-1999 of polyvinyl acetate emulsion adhesives for wood working. The research results indicated that fish bones as raw material are potential to be developed in the manufacture of fish glue.   Keywords: fish glue, bones, spanish mackerel, eastern little tuna, cobia